Die Darstellung Subsahara-Afrikas im deutschen Schulbuch : Gesellschaftslehre, Erdkunde, Geschichte und Politik der Sekundarstufe I (Gesamtschule) in Nordrhein-Westfalen - Awet, Kessete (Budrich UniPress Ltd., 2018)
Textbooks are of great importance for the design of the lessons within the school. Sub-Saharan Africa plays a rather subordinate role both in local society and in school books. The author, who fled from Eritrea, made this experience in the 1980s/90s as a student at a comprehensive school in Wuppertal. As part of his studies in social pedagogy, he found that this problem is also only marginally dealt with in the university context. Outside of school, too, Sub-Saharan Africa is portrayed in general media reporting as a crisis and disaster region, in which the share of European and Western countries in this situation largely plays a subordinate role and initiatives from Sub-Saharan Africa to solve problems are hardly mentioned .